EnCLASS: an innovative project merging 2 international surveys (HBSC/ESPAD) among French students. (13th November 2019) - Godeau, E; Ehlinger, V; Spilka, S
Abstract: Problem: For two decades, France has taken part in two "competing" school-based, cross-national surveys exploring the health behaviors and well-being of adolescent (Health Behavior in School-aged Children (HBSC) survey, 11-13-15 year-olds) and their substance use (European School Project on Alcohol and other Drugs (ESPAD), 15-16 year-olds). Description of problem: Since 2010, French data is provided at national level by grade rather than age. This allowed providing a continuous observation of health behaviors among adolescents, looking at the temporal spread of substance use and providing a better understanding of the role of school as a setting for adolescents' health. But the difficulty of participating every 4 years in two big surveys remained. Effects of changes: In 2018, France decided to conduct the 2 surveys in a unified and simultaneous way across middle- and high-school. This project is called 'National Survey in Middle- and High-school for Adolescents on Health and Substances', EnCLASS, explicit acronym easy to pronounce and remember in French. If the main objective of "merging" these surveys is to improve the monitoring of health behaviours and substance use throughout adolescence, it also allows a significant gain regarding preparation, coordination and organization of the fieldwork, hence of overall costs, while ensuring perfect comparability of data at international level. Evolution of data visualization on substance use will be used to illustrate the challenges and improvements of such a process, based on data collected in 2018 among more than 20, 000 representative secondary-school students. Lessons: In addition to a greater facility of interpreting and reading findings, presenting data throughout secondary school grades improves its impact and use in a public health perspective and allowing identifying operational targets for prevention and health promotion in schools, as classes are their main settings. Key messages: EnCLASS is unique in Europe, it ensures an excellent comparability of data at international level while providing an innovative national monitoring of adolescent health behavior, including drug use. Further, by its improved quality, perspective and relevance, EnCLASS can contribute to Public health policies analysis regarding school-students in France in a less expensive and better way.